RANCANG BANGUN ALAT PINDAH PASIEN MENGGUNAKAN SISTEM REM ELEKTRIK - Akbar Saputra, Fauzi; Muhida, Riza; Riza, Muhammad; Surya, Indra; Kunarto; Muhamad, Zein; Saputro, Harjono; Pratowo, Bambang; Mulyana (UNIB Press, 2025)
The mobility of patients with physical limitations is a major challenge in healthcare, particularly in the process of transferring from bed to wheelchair, toilet, or examination table. Based on data from BPS (2023) and Regsosek (2023), the number of people with disabilities and the elderly in Indonesia continues to increase, requiring innovation in assistive devices that are safe, ergonomic, and easy to use. This study designed a transfer chair with a solenoid-based electric brake system to improve the efficiency and safety of the patient transfer process. The research method included needs identification, structural and brake system design, fabrication, and functional testing. The calculation results show that the brake system with four 12V DC solenoids produces a total pressing force of 80 N and a braking torque of 6.10 Nm. Energy consumption for 5 minutes is 1.99 Wh with a minimum battery capacity requirement of 166 mAh. The static stability coefficient of 1.14 indicates the device is stable during use. The device is able to withstand static loads of up to 90 kg without brake function disruption and is in accordance with anthropometric data for the Indonesian population. This design contributes to the development of medical devices that are affordable and responsive to the needs of patients and medical personnel.